Current perspectives on the capabilities of high resolution XRF core scanners. (30th April 2019) - Croudace, Ian W.; Löwemark, Ludvig; Tjallingii, Rik; Zolitschka, Bernd
Abstract: The introduction and application of high resolution XRF core scanners has made an enormous contribution to palaeoclimate science over the last two decades. These core scanners have become essential analytical tools for the investigation of sedimentary and other natural cumulative records of environmental change. Their widespread adoption by the environmental and geoscience communities has had a significant impact on the ability to systematically record high resolution chemical profiles in marine and lake sediments and soils. The range of applications has broadened beyond sedimentology and palaeoclimatology and now extends into scanning samples of speleothems, corals, mumiyo mounds, rocks, sedimentary nodules, archaeological artefacts, tree sections and melt segregations. Other areas exploiting the capability of XRF core scanners are mineral exploration, geotechnical characterisation, soil remediation studies and carbon capture and storage research. As a consequence of their ability to efficiently determine detailed, non-destructive elemental records in sediments and soils, scientific papers published since the year 2000 now number more than 1000.